Rare-Metal (In, Bi, Te, Se, Be) Mineralization of Skarn Ores in the Pitkäranta Mining District, Ladoga Karelia, Russia - Vasily I. Ivashchenko (Minerals, 2021)
The results of the study of rare-metal (Bi, Te, Se. Be, In) mineralization of skarn deposits (Sn, Zn) in the Pitkäranta Mining District, genetically related to the Salmi anorthosite-rapakivi granite batholiths of Early Riphean age are reported. Minerals and their chemical composition were identified on the base of optical microscopy as well as electron microanalysis. The diversity of rare-metal ore mineralization (native metals, oxides, and hydroxides, carbonates, tellurides, selenides, sulfides, sulphosalts, borates, and silicates) in Pitkäranta Mining District ores is indicative of considerable variations in the physicochemical conditions of their formation controlled by the discrete-pulse-like supply of fluids. Bismuth, wittichenite, and matildite are the most common rare-metal minerals. Sulfosalts of the bismuthinite-aikinite series are represented only by its end-members. The absence of solid solution exsolution structures in sulfobismuthides suggests that they crystallized from hydrothermal solutions at low temperatures. Be (>10 minerals) and In (roquesite) minerals occur mainly in aposkarn greisens. Roquesite in Pitkäranta Mining District ores formed upon greisen alteration of skarns with In released upon the alteration of In-bearing solid sphalerite (Cu1+ In3+) ↔ (Zn2+, Fe2+) and chalcopyrite In3+ ↔ Fe3+ and 2Fe3+ ↔ (Fe2+, Zn2+) Sn4+ solutions. Sphalerite with an average In concentration of 2001 ppm, is a major In-bearing mineral in the ores.